Social Networking and Misinformation Challenges: Moroccan Students in Tertirary Education as a Case Study - El Kandoussi, Mohamed (European Scientific Journal, ESJ, 2023)
This paper focuses on examining how Moroccan university students approach the various social networking sites, including their self-perceived capacities to critically analyze and evaluate digital content in general and online news and information more specifically. The paper poses several research questions that all aim to investigate the issue under examination. This empirical endeavor used the survey as a research instrument to gather data, and presented a number of conclusions and recommendations for the Moroccan policy makers, stakeholders, and all concerned parties. The study further reported that most respondents advance by critically evaluating social media content and largely deploying various efficient verification measures and techniques. In the same vein, the majority of respondents highly rated their digital media perceived self-efficacy. Almost two thirds of the participants postulate that higher educational institutions should incorporate digital literacy skills in their curricula and syllabi.